Mechanical Properties of Coconut Shell Reinforced Unsaturated Polyester Composites with the Presence of Titanium Dioxide as Additional Filler. Issue 1 (February 2020) - Shahidan, Nurzarihah; Abu Bakar, Mohamad Bashree; Mohamed, Mazlan; Lazim, Azwan Mat; Janvekar, Ayub Ahmed
Abstract: Unsaturated polyester (UPE) composites filled with coconut shell (CS) powder was prepared by compression molding technique. To improve the mechanical and physical properties of CS-UPE composites, titanium dioxide (TiO2) filler was added. CS also undergo two types of chemical treatment which were alkaline (NaOH) and silane treatment. Fourier transform infrared (FTIR) was used to investigate the changes of fibers chemical constituents after the two chemical treatments have been done. CS-TiO2-UPE composites was characterized with physical testing (density, water absorption and thickness swelling), mechanical properties (tensile and flexural test) and scanning electron microscopy (SEM). Overall, the result shows that, the presence of CS and TiO2 filler in UPE composites demonstrated the highest density. For water absorption and thickness swelling study, it was observed that the treated CS-UPE composites showed lower water absorption properties in comparison to those of untreated CS-UPE composites. The presence of TiO2 filler showed an increased in those water absorption properties but still low compared to CS filled UPE. Both chemical treatment of CS caused a significant increase in the tensile and flexural properties. The presence of TiO2 filler demonstrated a significant improvement in modulus properties but at the expense of strength properties. SEM investigation has shown that the surface modification of CS has better fiber-matrix interaction. Thus, chemical treatments on the CS improve fiber/matrix adhesion of UPE composites.